Uji Efektivitas Antidiabetik Ekstrak Etanol Daun Asia Afrika (Vernonia amygdalina del) Terhadap Kadar Gula Darah Pada Mencit Putih Jantan (Mus musculus) - Humaira, Vilma; Abieasa, M Saka; Nofrida, Sri Nola (Universitas Sumatera Barat, 2022)
Diabetes occurs due to a lack of insulin, which is a substance produced by the pancreas to process blood sugar (glucose) into energy. In diabetes, sugar in the blood cannot be processed into energy normally, and its levels may continue to rise. This study aims to determine the effect of giving African Asian leaves on blood glucose levels in male mice (Mus musculus) induced with intraperitoneal alloxan. This research is an experimental study using experimental animals as research subjects. The mice were divided into four groups, each group consisting of 7 mice. Group I was the negative control, while Groups II, III, and IV were treated with doses of 60 mg/kg body weight, 70 mg/kg body weight, and 80 mg/kg body weight, respectively. One-way ANOVA test showed that the blocks within the treatment groups with significant p-values indicated differences between treatment groups with significant p-values (p < 0.05).